Primary hyperparathyroidism. - Branco, T (1992)
Primary hyperparathyroidism due to a solitary adenoma of the right inferior parathyroid gland was diagnosed in a 60 year old female, presenting a 4 year complaint of progressive disabling bone and joint pain. The diagnostic follow-up used in this case, including the imaging techniques, the clinical features and the medical and surgical management are presented and discussed.